O Silêncio por trás de uma tela : percepções de intérpretes educacionais de libras no cenário pandêmico da COVID-19 - Carmo, Lívia Silveira do (2022)
Researching education is somewhat challenging given the entanglements involved and some variables that arise in the course of the work. This study presents the professional experiences of four educational interpreters of Sign Language who worked in basic education in the city of Anápolis-Goiás, focusing on the period of emergency remote teaching (March/2020 to July/2021) implemented after the pandemic decree due to the spread of COVID-19. The general objective is to analyze how the educational interpreters of Libras acted during the remote teaching instituted with the pandemic of COVID-19 and the professional experiences lived in this period. The specific objectives of this study were: to evoke the historical background and the legal formation of the profession of Pound interpreters worldwide and nationally, as well as portray the history of deaf education over time; to present the pandemics that occurred throughout history contextualizing with the pandemic moment of COVID-19; and finally, to point out the professional experiences that were lived by the educational interpreters of Pounds in the execution of their work activities with remote teaching during the pandemic of COVID-19. The choice of educational interpreters as the focus of this study was made by understanding the importance of this professional in the learning process of deaf students and thus represent an important link in a moment that was atypical and challenging for all. The study emphasizes the representativeness of these professionals throughout history as well as their activity in the educational environment and in this perspective interconnecting them to teaching through screens in a pandemic scenario. The research presents an approximation to the phenomenological method and is based on the principles of a qualitative approach of exploratory nature. The theoretical support that references this study presents authors such as: Quadros (2004), Lacerda (2010, 2016, 2017), Strobel (2006, 2008, 2009), Skliar (2016), Perlin (2006), Tuxi (2009), Sacks (2010) who deal with the deaf and interpreters; Barata (2020), Ygua (2021), Rincon-Ferraz (2020), Neufeld (2020), Santos (2020) who address the theme of pandemic, among others who also presented relevance to this study. The empirical part was conducted through a reflective interview with four educational interpreters of Libras and data collection occurred with virtual meetings through the Google Meet platform with questions that aimed to understand the performance of interpreters during emergency remote teaching. Data analysis was based on Minayo's dialectical hermeneutics and it was possible to notice that during the period a higher than usual work overload was attributed to the interpreters who found themselves acting remotely and facing new and old issues. The results obtained indicated that while technology was a way for teaching to continue in the face of social isolation, there were, however, obstacles in the use of these new technological resources. The study identified and it is evident in the reflective interviews that, with the pandemic, there was an intensification of the already existing lack of a policy that enables the proper support of school institutions, as well as the families of deaf students, for the work of educational interpreters, aiming at the educational success of deaf students. Finally, it was pointed out the need for further research so that Libras interpreters can gain more space and representativeness in our society.